2010
DOI: 10.1103/physrevlett.105.155502
|View full text |Cite
|
Sign up to set email alerts
|

From Brittle to Ductile Fracture in Disordered Materials

Abstract: We introduce a lattice model able to describe damage and yielding in heterogeneous materials ranging from brittle to ductile ones. Ductile fracture surfaces, obtained when the system breaks once the strain is completely localized, are shown to correspond to minimum energy surfaces. The similarity of the resulting fracture paths to the limits of brittle fracture or minimum energy surfaces is quantified. The model exhibits a smooth transition from brittleness to ductility, also present in how much plastic deform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This paper is organized as follows. First, we examine the strain avalanches of the system away from criticality, and find that, depending on the short-range part of the interaction kernel, the model can exhibit a nonuniversal crossover from mean-field behavior at small stresses to nonmean-field behavior, similar to that observed in a lattice model for ductile fracture [29]. We then examine the nonmean-field behavior at criticality in greater depth, and present evidence that it is indeed universal, depending only on the large-scale nature of interactions.…”
Section: Introductionmentioning
confidence: 80%
“…This paper is organized as follows. First, we examine the strain avalanches of the system away from criticality, and find that, depending on the short-range part of the interaction kernel, the model can exhibit a nonuniversal crossover from mean-field behavior at small stresses to nonmean-field behavior, similar to that observed in a lattice model for ductile fracture [29]. We then examine the nonmean-field behavior at criticality in greater depth, and present evidence that it is indeed universal, depending only on the large-scale nature of interactions.…”
Section: Introductionmentioning
confidence: 80%
“…In contrary, the modeling and simulations can provide important information and details on the fracture process and mechanism, especially in the atomic scale process, which is not accessible by the current experimental instruments and methods. In parallel with the experimental studies, there are also many theoretical model and simulation efforts on the fracture process of BMGs [27,[29][30][31]179,250,269,270]. The studies involve in a large different scales from continuous modeling to atomistic simulations, and make up an important portion in understanding the fracture mechanism and macroscopic mechanical behaviors of BMGs and other glassy materials.…”
Section: Modeling and Simulations On Fracture Process Of Bmgsmentioning
confidence: 99%
“…This widely different strength of the components combined with appropriate coupling results in an improved damage tolerance which has a high relevance for applications [20,21]. It has been shown that in heterogeneous materials, varying the local mechanical response and of the amount of disorder of the components one * ferenc.kun@science.unideb.hu can achieve a transition from brittle to quasibrittle or even to ductile failure [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%